Metavermilia ogasawaraensis sp. nov. (Serpulidae: Sabellida: Polychaeta: Annelida) from deep-sea locations off Ogasawara Island, Japan with a literature overview of the genus - Nishi, Eijiroh; Kupriyanova, Elena; Tachikawa, Hiroyuki (Zootaxa, 2007)
A new species of the genus Metavermilia Bush, 1905 (Annelida, Polychaeta, Serpulidae) is described from deep-water locations (1600–1700 m) off Ogasawara Islands, Japan. The genus Metavermilia is characterized by a single synapomorphy, the structure of the opercular stalk (flat and ribbon-like) formed from the second dorsal branchial radiole. The Metavermilia ogasawaraensis n. sp., is most similar morphologically to M. nanshaensis in having a simple conical operculum covered with a brownish distal plate with a tubercle in the middle and short thoracic membranes. The two species differ from each other in details of tube morphology and thoracic uncini structure. The paper provides a key and a review of all 14 species currently known in the genus Metavermilia.